Strategies for Improving Teachers’ Professional Development in Higher Education Institutions in the Southwest Region of Cameroon - Sophie Ekume Etomes; Mou Charlotte Nsem (Educational Considerations, 2023)
The expansion of higher education institutions (HEIs) in Cameroon, and the continuous change in the curriculum to meet national and global needs, calls for a need for continuous professional development of teachers to handle these challenges. This study examined peer coaching and reflective teaching as strategies for improving teachers’ professional development in HEIs in the Southwest region of Cameroon. Questionnaires and an interview guide were used to collect data from 409 teachers and 37 heads of departments respectively. The Spearman’s rho test was used to test the hypotheses while the ordinary least square regression model was used to test the impact of reflective teaching and peer coaching on teachers’ professional development. Findings revealed that peer coaching and reflective teaching have a positive and significant impact on teachers’ professional development. However, the regression model shows that reflective teaching has more impact on teachers’ professional development. In addition, the practice is more in the private sector than the state HEIs. Therefore, it is recommended that peer coaching should be well planned and teachers should be provided with relevant resources to carry out the activity. It is also recommended that teachers should be trained on how to carry out reflective teaching for effective practice.
Keywords: Higher Education; Peer Coaching; Professional Development; Reflective Teaching